Productivity grwoth and efficiency changes in the Mongolian mobile communications industry - Badamasuren Byambaakhuu; Youngsun Kwon; Jaejeung Rho (International Telecommunications Society (ITS), 2012)
In the mid 1990s Mongolia has introduced competition in the telecommunications market by deregulating it and opening up its mobile communications market to foreign direct investments. Since this policy reform, mobile service penetration has grown fast, recently exceeding 100 % penetration rate and mobile communications service has become the biggest among telecommunications services in Mongolia. Latest periods of the industry have been witnessing strong competition among the mobile service providers and challenge for reaching customers in remote areas of the country. On the other hand, the mobile service providers are uncertain for efficiency of their investments and benefits from competition. Policy and regulatory departments are unaware productivity growth of the sector which is crucial for the next policy and regulatory decisions. Considering such situation, this study estimates productivity growth and efficiency changes in the mobile communications industry of Mongolia over the period of 2007-2011 using firm level data and employing a Malmquist total factor productivity index method. By determining the changes in total factor productivity (TFP) growth and its components, technical change and technical efficiency change, we find that the productivity increased about 44.7 percent during the study period or nearly 9 percent annually. Our research identifies that a scale change component played as a most significant source of the TFP growth in the market. In addition, our study reveals a fluctuation pattern of the productivity growth caused by catch-up effect and technology-change components during the study period. The results of the study indicates effectiveness of a competition policy for the mobile telecommunications market with shared telecommunications network for gaining the productivity growth which may provide some lessons for similar economies as Mongolia.
Keywords: 330; Mongolian mobile communications; Total factor productivity; Malmquist TFP index.